2020
DOI: 10.1038/s41593-020-0617-7
|View full text |Cite
|
Sign up to set email alerts
|

Orexin signaling in GABAergic lateral habenula neurons modulates aggressive behavior in male mice

Abstract: Heightened aggression is characteristic of multiple neuropsychiatric disorders and can have various negative effects on patients, their families, and the public. Recent studies in humans and animals have implicated brain reward circuits in aggression and suggest that, in subsets of aggressive individuals, domination of subordinate social targets is reinforcing. Here, we show that in male mice, orexin neurons in the lateral hypothalamus activate a small population of glutamic acid decarboxylase 2 (GAD2)-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 62 publications
8
117
1
Order By: Relevance
“…This functional heterogeneity within aminergic neurons provides flexibility in control of aggression according to social experience. Our findings parallel recent vertebrate studies reporting lateral habenula subpopulations that respond in opposite directions during aggressive encounters 36,37 .…”
Section: Nvy Marks Aggression-suppressing Neuronssupporting
confidence: 91%
“…This functional heterogeneity within aminergic neurons provides flexibility in control of aggression according to social experience. Our findings parallel recent vertebrate studies reporting lateral habenula subpopulations that respond in opposite directions during aggressive encounters 36,37 .…”
Section: Nvy Marks Aggression-suppressing Neuronssupporting
confidence: 91%
“…Recently, Flanigan et al showed that the activation of GABAergic neurons in the LHb promoted male-male aggression and these GABAergic neurons were inhibitory within the LHb and dampened the activity of the LHb overall. 74 These data suggest that there are local circuits within the LHb. There is consensus that most of the neurons in the RMTg are GABAergic.…”
Section: Differences Between the Lhb And The Rmtgmentioning
confidence: 91%
“…The anxiety level and locomotor function of the subjects were assessed by using the open-field test (Flanigan et al, 2020; Walsh et al, 2018). Briefly, a square open field (50 cm × 50 cm × 25 cm) was virtually subdivided into 16 even square.…”
Section: Methodsmentioning
confidence: 99%